The science of prevention for children and youth - Sanson, A.; Havighurst, S.; Zubrick, Stephen (The University of Sydney, 2011)
The high prevalence of social, emotional and behavioural health problems in children and young people in Australia, and the high cost and relative ineffectiveness of treatments to ‘cure’ them, lead to the conclusion that the most efficient and cost effective approach is to prevent them from occurring. The challenge is in determining what to prevent and how to do so. While there are complex social and political aspects to prevention, it must also be guided by a solid scientific basis. This paper makes the case that prevention science provides a framework for ensuring that prevention initiatives are founded on robust evidence and implemented in a way that will allow progressive growth in knowledge of ‘what works’ in prevention. The paper examines some of the opportunities and challenges in a shift to an evidence-based prevention agenda to improve the lives of children and young people.